2010
DOI: 10.17796/jcpd.34.4.p35436j05010u562
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Comparison of Self versus Professionally Applied Remineralizing Materials

Abstract: Objective: To compare the effect of 4 remineralizing materials on the incipient artificial carious lesion and its proximal sound enamel when used with fluoride dentifrice. Study Design: Models mimicking proximal contact were made, each of which was placed with an artificial carious specimen in contact with a sound enamel specimen. Each carious specimen was treated with one of four materials: glass ionomer cement (GIC), resin modified glass ionomer cement (RMGIC), 5000 ppm sodium fluoride (F-gel)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
1
1
Order By: Relevance
“…However these results were not in agreement with Trairatvorakul et al, 2010 (11) , who found that the CPP-ACP was the least efficacious treatment in both preventing demineralization of the intact enamel specimens and in remineralizing the artificial carious specimens. This difference was attributed to the fact that their study was performed in the absence of an oral microbial environment or plaque accumulation on the tooth surfaces, which may have resulted in decreased CPP-ACP adherence to the tooth surfaces since CPP-ACP has been suggested to be incorporated into plaque by binding to bacterial cell surfaces and to intercellular plaque matrix.…”
Section: Discussioncontrasting
confidence: 57%
“…However these results were not in agreement with Trairatvorakul et al, 2010 (11) , who found that the CPP-ACP was the least efficacious treatment in both preventing demineralization of the intact enamel specimens and in remineralizing the artificial carious specimens. This difference was attributed to the fact that their study was performed in the absence of an oral microbial environment or plaque accumulation on the tooth surfaces, which may have resulted in decreased CPP-ACP adherence to the tooth surfaces since CPP-ACP has been suggested to be incorporated into plaque by binding to bacterial cell surfaces and to intercellular plaque matrix.…”
Section: Discussioncontrasting
confidence: 57%
“…This maintains high concentrations of calcium and phosphate ions in subsurface lesions promoting enamel remineralization 9) . Self-applied CPP-ACP and professionally-applied GI have remineralizing ability as assayed by reduction in lesion area or depth 10,11) . However, their effect on mineral density is unclear.…”
Section: Introductionmentioning
confidence: 99%